Impact of electro-conductive nanoparticles additives on anaerobic digestion performance - A review - Hassanein, Amro; Naresh Kumar, A.; Lansing, Stephanie (Bioresource technology, 2021)
[Display omitted] •Conductive NPs potential to improve AD performance was critically discussed.•Impact of different NPs and sizes on AD biogas quantity and quality are elucidated.•The interactions of AD microorganisms and DIET with the aid of NPs were reviewed.•The role of NPs in biochemical pathways direction and metabolites utilization are covered. Anaerobic digestion (AD) is a biochemical process that converts waste organic matter into energy-rich biogas with methane as the main component. Addition of electric electro-conductive, such as that nanoparticles (NP), has been shown to improve biogas generation. Interspecies electron transfer and direct interspecies electron transfer (DIET) using conductive materials is one of the mechanisms responsible for observed increases in CH4. This article discusses the effect of the type and size of electro-conductive NPs on improving microbial degradation within AD systems, as well as the effect of electro-conductive NPs on microbial community shifts and syntrophic metabolism. Limitations and future perspectives of using NPs in an AD system is also discussed.